Neuropsychiatric Manifestation Screening among Systemic Lupus Erythematosus Patients in Hasan Sadikin General Hospital Bandung - Septian Dwi Putra; Mulya Nurmansyah Ardisasmita; Laniyati Hamijoyo (Indonesian Rheumatology Association, 2017)
Background: Systemic Lupus Erythematosus (SLE) is an autoimmune diseases caused by deposition of immune complex with the involvement of various organ system and certain autoantibodies production. One of the most significant manifestation is neuropsychiatricsymptoms, known as NPSLE (Neuropsychiatric Systemic Lupus Erythematosus). This study aims to portray the distribution of neuropsychiatric manifestation of SLE patients using a screening method in Hasan Sadikin General Hospital.Method: An observative, descriptive categoric study, with consecutive sampling were done. Data were collected by spreading the questionnaire to subjects diagnosed as SLE who visiting Hasan Sadikin General Hospital during August-October 2016 and by tracingtheir medical records. Data analyzed included age, sex, education background, duration of lupus, diagnosis criteria, ongoing therapy, and neuropsychiatric manifestation.Result: Samples volunteered in this study were 97 patients. Of them 94 patients (96.9%) were women and 47 patients (48.5%) were senior high school graduated. Most common diagnosis criteria found was positive ANA test (91.8%). Most necessary ongoing therapygiven was methylprednisolone (96.9%). Common neuropsychiatric manifestations were mood disorders (73,2%), headache (57,7%), and mononeuropathy (51,5%).Conclusion: The common psychiatric, central nervous, and peripheral nervous manifestations were mood disorder, headache, and mononeuropathy, respectively.Keywords: Neuropsychiatry, NPSLE Screening,Systhemic Lupus Erythematosus